Does a school-based intervention to engage parents change opportunity for handwashing with soap at home? Practical experience from the Mikono Safi trial in Northwestern Tanzania. - Yovitha Sedekia; Saidi Kapiga; Onike Mcharo; Kenneth Makata; Belen Torondel; Robert Dreibelbis; Elialilia Okello (PLoS Neglected Tropical Diseases)
Background School-based de-worming is advocated as a strategy for reducing the burden of soil-transmitted helminth (STH) infections among children. However, re-infection tends to occur rapidly, suggesting that comprehensive water, sanitation, and hygiene (WASH) improvements may be needed to prevent this. We qualitatively assessed the influence of parental engagement activities on parents' motivation to improve WASH infrastructure and hygiene practices at home in the context of a school-based de-worming programme. Methodology We conducted a longitudinal qualitative study nested within the Mikono Safi trial, designed to assess the effect of a WASH intervention on STH infection prevalence in children. Meetings were organized for parents/guardians at schools where they were given information about STH infection, the role of WASH in STH infection prevention, and actionable steps they could take at home. During the meetings, parents/guardians received information about their own child's STH infection status. Twenty purposively selected households were visited and interviewed 3 times over a period of about 8-months. We employed thematic analysis; findings are reported following the Capability-Opportunity-Motivation and Behaviour (COM-B) framework. Principal findings The engagement strategy improved parents'/guardians' knowledge and skills about handwashing with soap and its benefits. Parents/guardians reported that the sessions had motivated them to improve WASH infrastructure at home. Of 20 households included in this study, 17 renovated or built new latrines and 18 installed handwashing facilities. However, only 8 households established and maintained handwashing stations with both soap and water at 8 months. Conclusions The engagement of parents/guardians in a school-based WASH education intervention as part of the Mikono Safi trial resulted in increased knowledge and motivation about handwashing and sanitation. This led to improvements in sanitation facilities and handwashing opportunities at home. However, long-term success in provision of water and soap was limited, indicating that sustained engagement may be required to encourage households to ensure these materials are consistently available at home.